Pengaruh Return On Equity (ROE), Earning Per Share (EPS) dan Debt To Equity Ratio (DER) Terhadap Harga Saham (Studi Empiris Pada Perusahaan Industri Makanan Olahan yang Terdaftar di Bursa Efek Indonesia Tahun 2018 – 2020) - Ratih Kusumastuti; Sri Devi Andriani; Riski Hernando (Owner : Riset dan Jurnal Akuntansi, 2023)
This study is a quantitative study that aims to determine the effect of return on equity (ROE), earning per share (EPS) and debt to equity ratio (DER) on stock prices. The stock price is measured using the natural logarithm of the closing price. The population in this study are procesed food industry companies listed on the Indonesia Stock Exchange in 2018 – 2020. The sampling technique used is purposive sampling. The sample in this study amounted to 51 samples of 17 companies multiplied by accessing the company’s financial statement through the website of the Indonesia Stock Exchange (IDX). The data analysis technique used in this study is multiple linear regression analysis with the help of SPSS version 25 program. The result of this study indicate that simultaneously return on equity, earning per share and debt to equity ratio have an effect on stock prices. Partially, the return on equity has an effect on stock price. Earning per share and debt to equity ratio partially have no effect on stock prices. Keywords: Return On Equity, Earning Per Share, Debt To Equity Ratio, Stock Price